1997
DOI: 10.1097/00000658-199706000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Crohn's Disease and Ulcerative Colitis Are Associated With the DNA Repair Gene MLH1

Abstract: This study identifies a novel genetic and clinical association between MLH1 and inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 13 publications
2
24
0
1
Order By: Relevance
“…17 Satsangi et al observed the strongest evidence of linkage in CD families, 2 while in our material the greatest evidence of linkage seems to be from the mixed families, which may reflect greater average size of the families in this group. The chromosome 3 region has also raised attention in an association study by Pokorny et al 30 who reported an increase of a specific haplotype, constructed from the alleles of the marker D3S1611 and the HNPCC (hereditary non-polyposis colon cancer) gene MLH1, in IBD patients. The chromosome 3p21 region seems intriguing as it harbours, in addition to MLH1, other interesting candidates genes including those encoding a cluster of chemokine receptors, and a G protein subunit a i2 (GNAI2) the deficiency of which causes an UC-like phenotype in knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…17 Satsangi et al observed the strongest evidence of linkage in CD families, 2 while in our material the greatest evidence of linkage seems to be from the mixed families, which may reflect greater average size of the families in this group. The chromosome 3 region has also raised attention in an association study by Pokorny et al 30 who reported an increase of a specific haplotype, constructed from the alleles of the marker D3S1611 and the HNPCC (hereditary non-polyposis colon cancer) gene MLH1, in IBD patients. The chromosome 3p21 region seems intriguing as it harbours, in addition to MLH1, other interesting candidates genes including those encoding a cluster of chemokine receptors, and a G protein subunit a i2 (GNAI2) the deficiency of which causes an UC-like phenotype in knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…(20)(21)(22)(23) Recentemente, novas pesquisas tentam atribuir como causas a mutação da integrina beta-2, (24) de populações de monócitos CD14+ (25) e do gene de reparo do DNA MLH-1. (26) Histologicamente, a DCM se caracteriza por granulomas cutâneos não-caseosos, com células gigantes multinucleadas de Langhans e do tipo corpo estranho, os quais se distribuem na derme superficial, derme profunda e no tecido adiposo, similares aos granulomas do trato gastrointestinal. (1,2,4-7,9,12,16) Outras caracterís-ticas descritas são o infiltrado rico em eosinófilos e degeneração cística do colágeno (necrobiose).…”
Section: Discussionunclassified
“…[16][17][18][19][20][21][22][23] However, the reported frequency of MSI-H, a consequence of a defective mismatch repair (MMR) system (notably MLH1 or MSH2), and MSI-L, a consequence in part of O 6 -methylguanine-DNA methyltransferase (MGMT) deficiency, 24 has varied considerably from 9 to 50%, and 11 to 85%, respectively. 22,[25][26][27] In situation of considerable genetic heterogeneity within a sample, collection of samples without microdissection could possibly obscure the findings of MSI. 28,29 In fact, analysis of mixed MSI-L components could result in a false diagnosis as MSI-H. To verify true MSI status and to clarify the significance of MSI in colitic carcinogenesis, precise analysis of individual microfoci from various pathological lesions (including stroma) is required.…”
mentioning
confidence: 99%